2016
DOI: 10.1007/s10995-016-1926-z
|View full text |Cite|
|
Sign up to set email alerts
|

Moderate and Vigorous Intensity Exercise During Pregnancy and Gestational Weight Gain in Women with Gestational Diabetes

Abstract: Objectives To estimate the associations of moderate and vigorous intensity exercise during pregnancy with the rate of gestational weight gain (GWG) from gestational diabetes (GDM) diagnosis to delivery, overall and stratified by prepregnancy overweight/obesity. Methods Prospective cohort study with physical activity reported shortly after the GDM diagnosis and prepregnancy weight and post-diagnosis GWG obtained from electronic medical records (n= 1,055). Multinomial logistic regression models in the full coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 36 publications
0
32
2
Order By: Relevance
“…However, more than half of women do not receive counseling about physical activity during the prenatal service before GDM diagnosis, and more than 60% do not receive counseling after the diagnosis. In addition, for those with GDM, light walking for 25 to 40 minutes, three or four times a week, resulted in a decrease in the need for insulin, and there are suggestions that the best results may be achieved with vigorous intensity exercises . Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM and in women with GDM who are overweight, including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more than half of women do not receive counseling about physical activity during the prenatal service before GDM diagnosis, and more than 60% do not receive counseling after the diagnosis. In addition, for those with GDM, light walking for 25 to 40 minutes, three or four times a week, resulted in a decrease in the need for insulin, and there are suggestions that the best results may be achieved with vigorous intensity exercises . Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM and in women with GDM who are overweight, including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for those with GDM, light walking for 25 to 40 minutes, three or four times a week, resulted in a decrease in the need for insulin, 35 and there are suggestions that the best results may be achieved with vigorous intensity exercises. 11,36 Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM 37 and in women with GDM who are overweight, 38 including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk. 9 However, our findings indicated that less than half the participants received counseling for physical activity practice before or after the diagnosis of GDM, behavior that could help in the management of GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once gestational diabetes mellitus is diagnosed, either aerobic or resistance training can improve insulin action and glycemic control (129). In women with gestational diabetes mellitus, particularly those who are overweight and obese, vigorousintensity exercise during pregnancy may reduce the odds of excess gestational weight gain (130). Ideally, the best time to start physical activity is prior to pregnancy to reduce gestational diabetes mellitus risk (131), but it is safe to initiate during pregnancy with very few contraindications (126).…”
Section: Resistance Exercise Trainingmentioning
confidence: 99%
“…The baseline GEM survey included a self-administered Pregnancy Physical Activity Questionnaire [17, 21, 22] that assessed key components of physical activity (i.e., type, frequency, duration and intensity) and is recommended for use in pregnancy and the postpartum [23]. The GEM Pregnancy Physical Activity Questionnaire asked women to report time spent in 36 population-appropriate activities over the past three months (questions on yoga/Pilates, use of cardiovascular exercise machines, aerobic exercise classes, weight lifting/resistance exercises and team sports were added to the original Pregnancy Physical Activity Questionnaire).…”
Section: Methodsmentioning
confidence: 99%